Neopterin and kynurenine in serum and urine as prognostic biomarkers in hospitalized patients with delta and omicron variant SARS-CoV-2 infection - Krčmová, Lenka Kujovská; Matoušová, Kateřina; Javorská, Lenka; Šmahel, Petr; Skála, Mikuláš; Koblížek, Vladimír; Škop, Jan; Turoňová, Dorota; Gančarčíková, Markéta; Melichar, Bohuslav (Clinical chemistry and laboratory medicine, 2023)
OBJECTIVES: Currently, no biomarker or scoring system could clearly identify patients at risk of progression to a severe coronavirus disease (COVID)-19. Even in patients with known risk factors, the fulminant course cannot be predicted with certainty. Analysis of commonly determined clinical parameters (frailty score, age, or body mass index) together with routine biomarkers of host response (C-reactive protein and viral nucleocapsid protein) in combination with new biomarkers neopterin, kynurenine, and tryptophan, could aid in predicting the patient outcome. METHODS: In 2021 and 2022, urine and serum samples were prospectively collected on 1st to 4th day after hospital admission in 108 consecutive COVID-19 patients hospitalized at the University Hospital Hradec Králové, Czech Republic. Delta and omicron virus variants were studied. Neopterin, kynurenine and tryptophan were determined by liquid chromatography. RESULTS: A significant correlation was observed between urinary and serum biomarker concentrations. Urinary and serum neopterin, kynurenine and kynurenine/tryptophan ratio were significantly (p≤0.05) higher in patients who subsequently needed oxygen therapy vs. patients without oxygen therapy. These parameters were also significantly increased in patients who died during the hospitalization compared to survivors. Complex equations have been derived using the investigated biomarkers and other clinical or laboratory parameters to predict the risk of subsequent oxygen therapy or death during hospitalization. CONCLUSIONS: Present data demonstrate that neopterin, kynurenine and kynurenine/tryptophan ratio in the serum or in the urine represent promising biomarkers in the management of COVID-19 that may help to guide important therapeutic decisions.
Keywords: neopterin; biologické markery; Neopterin; prognóza; lidé; Kynurenine; kyslík; Prognosis; kynurenin; Biomarkers; Oxygen; COVID-19; Humans; SARS-CoV-2; kynurenine; urine; Tryptophan; prognosis; tryptofan; HPLC